Short-term uncleaned signal to noise threshold ratio based end-to-end time domain speech enhancement in digital hearing aids - Padmaja Nimmagadda; Kondru Ayyappa Swamy; Samuda Prathima; Sushma Chintha; Zachariah Callottu Alex (Institute of Advanced Engineering and Science, 2022)
This paper presents the improvements in the combined solution for the noise estimation and the speech enhancement in digital hearing aids in time domain. This study focuses on the single channel statistical temporal speech enhancement using adaptive Wiener filtering. In this technique, the noise is updated based on the short-term uncleaned signal to noise threshold ratio (ST-USNTR) of the frame. It works best if and only if the back ground noise level is low compared to that of speech of interest. We considered the time domain algorithms in order to consider the time varying nature of speech signal. The performance of the proposed algorithm is evaluated for speech signal with seven ty pes of noises and three signal to noise ratios (SNR) levels in each type of noise. From the results, it is clear that the basic level of adaptive speech enhancement is obtained using statistical parameters of noisy speech without the need for reference input.